Evidence that the aesthetic preference for Hogarth's Line of Beauty is an evolutionary by-product - Hübner, Ronald; Lewis, David M G; Al-Shawaf, Laith; Semchenko, Ayten Yesim; Flores, Jonathon (Scientific reports, 2023)
In 1753, artist William Hogarth declared a specific S-shaped line to be the 'Line of Beauty' (LoB). Hogarth's assertion has had a profound impact on diverse fields over the past two and a half centuries. However, only one recent (2022) study has investigated whether Hogarth's assertion accurately captures humans' actual aesthetic preferences, and no research has explored why people find the LoB beautiful. We conducted two studies testing the hypothesis that the LoB's perceived beauty is an incidental by-product of cognitive systems that evolved to attend to fitness-relevant morphological features in people. In Study 1, we replicated the finding that female bodies whose lumbar curvature approximates the biomechanical optimum for dealing with the exigencies of pregnancy are rated as more attractive. In Study 2, we found that abstract lines extracted from these bodies were perceived as more beautiful than other lines. These results suggest that the preference for Hogarth's LoB is an incidental by-product of psychological mechanisms that evolved for other purposes. More broadly, these findings suggest that an evolutionary psychological approach - in particular the concept of evolutionary by-product - may be useful for understanding, explaining, and predicting people's aesthetic preferences for certain abstract symbols, which otherwise might seem arbitrary and inexplicable.
Keywords: estetika; Exercise; Esthetics; lidé; cvičení; těhotenství; Biological Evolution; umění; Pregnancy; Beauty; Art; Humans; krása; biologická evoluce; ženské pohlaví; Female